Characterization of the double purpose bovine system and reproductive evaluation of bulls in the state of Chiapas - Ruiz -Sesma, Benigno; Herrera-Haro, José G.; Rojas-Martínez, Reyna I.; Mendoza-Nazar, Paula; Ruiz-Sesma, Herbey; Ruiz-Hernández, Horacio (Ecosistemas y Recursos Agropecuarios, 2021)
A study was carried out in a dual purpose system, at the GGAVATT in Villaflores, Chiapas, Mexico. The aims were to know the farmer’s selection approaches, the sire’s reproductive status. A direct sampling survey was carried out in 36 farmers, randomly chosen from a total of 160 producers, according to a stratified sampling design with Neyman allocation. The opinion survey included the approach as producer’s made the selection of sire’s, heifer’s replacement and productive indicators. The reproductive evaluation included scrotal circumference (CE), corporal condition (DC) and semen quality depending of genetic type. The results showed a dual purpose production system, based on Brown Swiss breed and their cross with Zebu. The farm average size was 32.9 ha and herd’s size 51.6 animals. The average milk production was 6.98 kg cow-1 d-1, milking 1.2 times d-1, the lactation period was 205 days and the heifer’s age at first service was 28.8 months. The reproductive evaluation showed that 13.9 % of the bulls had reproductive problems due to the inefficacy of the management system mainly the inopportune diagnostic of the bull’s fertility. It was concluded that main emphasis on the farmer’s selection were based on milk yield and calves weaning weight, which was based on a subjective criteria due to lack of production records. The high presence of sires with reproductive problems is must due there is not mating breeding season defined in this area